Analysis of Challenges and Support in the Implementation of Computer-Based National Assessment (CNA) for Students at Ngijo 01 Gunungpati Public Elementary School - Hasna Mutia Insani; Moh. Farizqo Irvan (FKIP - Universitas Riau, 2026)
This study investigates the effectiveness of the Adaptive Gamified Problem-Based Learning model in improving students’ critical thinking skills and mathematical reasoning in elementary mathematics learning. The research was conducted using a quasi-experimental design involving control and experimental groups, both receiving pretests and posttests. Validity and reliability testing indicated that all instrument items met statistical requirements. Descriptive results showed that the experimental group achieved higher posttest gains in both critical thinking and mathematical reasoning compared to the control group. Normality and homogeneity tests confirmed that the data were suitable for parametric analysis. Paired sample t-tests revealed significant improvements within each group, while independent sample t-tests indicated that the experimental group outperformed the control group with strong statistical significance. Pearson correlation analysis further demonstrated a strong positive relationship between critical thinking and mathematical reasoning, indicating that improvements in one skill are associated with enhancements in the other. Overall, the findings highlight that integrating adaptive gamification into the problem-based learning framework effectively enhances students’ higher-order thinking skills. The study concludes that this model is pedagogically beneficial for supporting deeper conceptual understanding, sustained engagement, and improved problem-solving performance in mathematics.